2000
DOI: 10.1086/317565
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid: A Precursor of Oxalate in Crystal Idioblasts ofYucca torreyiin Liquid Root Culture

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Phloem translocation of L-ascorbic acid thus appears to be crucial for its supply to sink organs. Ascorbic acid largely provides the substrate for oxalic acid biosynthesis in plants and is used for calcium oxalate formation (Horner et al, 2000). In this study, the concentration of endogenous ascorbic acid (14 mg 100 g -1 fresh weight) detected in E8.2-OXDC fruit, even after a 10% to 12% reduction, was within the normal range reported for ripe tomato fruits (Zhang et al, 2011;Cronje et al, 2012) and so is not expected to have any negative nutritional effect in the E8.2-OXDC fruit.…”
Section: Engineering Of Oxdc Balances Organic Acid By Affecting Carbosupporting
confidence: 72%
“…Phloem translocation of L-ascorbic acid thus appears to be crucial for its supply to sink organs. Ascorbic acid largely provides the substrate for oxalic acid biosynthesis in plants and is used for calcium oxalate formation (Horner et al, 2000). In this study, the concentration of endogenous ascorbic acid (14 mg 100 g -1 fresh weight) detected in E8.2-OXDC fruit, even after a 10% to 12% reduction, was within the normal range reported for ripe tomato fruits (Zhang et al, 2011;Cronje et al, 2012) and so is not expected to have any negative nutritional effect in the E8.2-OXDC fruit.…”
Section: Engineering Of Oxdc Balances Organic Acid By Affecting Carbosupporting
confidence: 72%
“…S3), suggesting the root as another possible source of the CaOx crystal carbon. As previously reported, roots not only contain CaOx crystals but they can also metabolize oxalate (Franceschi, 1989;Horner et al, 2000;Horner, 1984, 1985).…”
Section: Resultsmentioning
confidence: 59%
“…The development of crystal idioblasts, including the structural changes of the idioblasts and the morphological development of the crystals, has been reported for many plant species (Horner and Wagner, 1995). In crystal idioblasts, morphologically unique plastids, termed crystalloplastids (Arnott, 1966), were observed in the roots of Vanilla planifolia (Mollenhauer and Larson, 1966;Kausch and Horner, 1983a), Monstera deliciosa (Mollenhauer and Larson, 1966) and Yucca torreyi (Arnott, 1966;Kausch and Horner, 1984;Horner et al, 2000), and in leaves of Typha angustifolia (Kausch and Horner, 1983b).…”
mentioning
confidence: 99%
“…The result of the L-1-14 C ascorbic acid labeling (Horner et al, 2000) suggested that crystalloplastids in roots of Yucca may participate in some way in the conversion of the ascorbic acid to oxalate and in the transfer of oxalate to the cell vacuoles. Kausch and Horner (1983b) reported that the crystalloplastids may be involved in the formation of vacuolar mucilage surrounding the crystals in raphide crystal idioblasts in Typha.…”
mentioning
confidence: 99%